2012
DOI: 10.1007/s12110-012-9148-6
|View full text |Cite
|
Sign up to set email alerts
|

Subsistence and the Evolution of Religion

Abstract: We present a cross-cultural analysis showing that the presence of an active or moral High God in societies varies generally along a continuum from lesser to greater technological complexity and subsistence productivity. Foragers are least likely to have High Gods. Horticulturalists and agriculturalists are more likely. Pastoralists are most likely, though they are less easily positioned along the productivity continuum. We suggest that belief in moral High Gods was fostered by emerging leaders in societies dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(78 citation statements)
references
References 33 publications
3
70
2
Order By: Relevance
“…Previous cross-cultural studies have found a correlation between MHGs and a range of measures of social complexity [5,9,11], supporting both the BSP and MHG hypotheses. However, these studies are problematic for two reasons.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Previous cross-cultural studies have found a correlation between MHGs and a range of measures of social complexity [5,9,11], supporting both the BSP and MHG hypotheses. However, these studies are problematic for two reasons.…”
Section: Introductionsupporting
confidence: 61%
“…First, previous research has relied on standard correlational techniques that are unable to get at the direction of causality [5,9,11]. Second, previous rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 99%
“…Although one possible explanation for these results is that MHGs facilitate social complexity, another is that social complexity makes cultures more likely to adopt MHGs. Second, these studies are ether based on a single dataset called the Ethnographic Atlas or a subset of this dataset known as the Standard Cross-Cultural Sample (17,18,35,38). The MHGs in these datasets are almost all derived from the closely related family of Abrahamic religions-Christianity, Judaism, and Islam (37).…”
Section: Big(ish) Data and Need For Computational Methodsmentioning
confidence: 99%
“…We consider the following covariates in our models, all positively correlated with a belief in moralizing high gods: political complexity (17), practice of agriculture (17), and recognition of rights to movable property, as measured by the practice of animal husbandry (9,16). Our analysis is based on a global cross-cultural sample of 583 human societies (36,37) that occupy a range of different habitats and are exposed to a wide array of environmental conditions ( Fig.…”
Section: Significancementioning
confidence: 99%
“…In particular, religious beliefs are thought to be a powerful mechanism for the enforcement of social rules (12)(13)(14)(15). In support of these ideas, comparative studies have shown that a belief in moralizing high gods-defined as supernatural beings believed to have created or govern all reality, intervene in human affairs, and enforce or support human morality (7)-tends to be more prevalent among societies that recognize rights to movable property (9,16), as well as in those that exhibit higher levels of political complexity (17), subsistence productivity (17), and norm compliance (18). In addition, psychological experiments have found that moralizing high god concepts can reduce levels of cheating (14) and increase willingness to be fair (19) and to cooperate (13).…”
mentioning
confidence: 99%